Knowledge, attitudes and practices in food safety and the presence of coagulase-positive staphylococci on hands of food handlers in the schools of Camaçari, Brazil - Soares, Lilian S.; Almeida, Rogeria C.C.; Cerqueira, Ellayne S.; Carvalho, Joelza S.; Nunes, Itaciara L. (Food control, 2012)
The aim of this study was to evaluate the level of knowledge, attitudes and practices in food safety and the presence of coagulase-positive staphylococci species on the hands of food handlers in the municipal schools of Camaçari, Bahia in northeast Brazil. This study was conducted in two stages. In the first stage, 166 food handlers were interviewed via a questionnaire to assess their food safety knowledge, attitudes and practices. In the second phase, the presence of coagulase-positive staphylococci species on the hands of food handlers was determined. The results indicated that most of the handlers had been trained (92.2%), but the level of knowledge was insufficient; the average proficiency score was <70% accuracy. Attitude received the highest scores, and no handler had a score below 50.0%. Logistic regression analysis showed that the level of education and specific subject expertise of the handlers were associated with general knowledge about food safety. Food handler overall had positive attitudes on food safety with all scores above 50.0%. Despite a high prevalence of training and positive attitudes about food safety, 53.3% of the hand samples showed the presence of coagulase-positive staphylococci. No associations were found between the knowledge attitudes and practices of food handlers and the presence of the pathogen on their hands. The results showed inadequate sanitary practices of food handlers, highlighting the need to review the current model for training food handlers and to improve accessibility to sinks and supplies to ensure proper hygiene. ► We assessed food safety knowledge, attitudes and practices of food handlers. ► Presence of staphylococci on the hands of handlers from schools was evaluated. ► Logistic regression showed that education and expertise influenced the knowledge. ► 53.3% of the food handlers had attended training had staphylococci on their hands. ► The results highlighting the need to review the model of training food handlers.